2022
DOI: 10.31272/jeasd.25.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Methylene Blue Dye Using an Advanced Oxidation Process (Ultraviolet Light and Hydrogen Peroxide)

Abstract: Photolysis of methylene blue was studied by using an advanced UV/H2O2 oxidation process. This study investigated different initial dye concentrations (I0, 20, 30 ppm) using different concentrations of H2O2 (10 %, 30%, 50 %) in three additions (5 mL, 10 mL, 15 mL). The results showed that the degradation efficiencies of this dye at different concentrations were as follows: 99.86 % at 10 ppm using 15 mL of 10 % H2O2 after 60 min, 99.22 % at 20 ppm using 15 mL of 30 % H2O2 for 60 min, and 98.90 % at 30ppm using 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They can be categorized into physical, chemical, biological, or hybrid methods [17]. Those methods, including but not limited to, coagulation [18], adsorption [19], photolysis [20], electrochemical [21], biological treatment [22], membrane processes [23], and their hybrids [24][25][26] have all been investigated. Amongst them, adsorption is used for its efficiency, easy processing, and cheap cost [27], while membranes are used for their low required energy, low required space, reduced chemical consumption, and relatively low cost of operation [6].…”
Section: Introductionmentioning
confidence: 99%
“…They can be categorized into physical, chemical, biological, or hybrid methods [17]. Those methods, including but not limited to, coagulation [18], adsorption [19], photolysis [20], electrochemical [21], biological treatment [22], membrane processes [23], and their hybrids [24][25][26] have all been investigated. Amongst them, adsorption is used for its efficiency, easy processing, and cheap cost [27], while membranes are used for their low required energy, low required space, reduced chemical consumption, and relatively low cost of operation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ersöz and Altintas [5] used Ag-doped ZnO nanofibers for the photodegradation of MB and concluded that adding H 2 O 2 to the process produces reactive OH radicals that enhance MB degradation. Hanadi et al [6] reported the photolysis of MB using a UV/H 2 O 2 system and achieved 100% efficiency of MB degradation. Cao et al [7] synthesized ZnFe 2 O 4 /BiVO 4 nanocomposites for MB photodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…These advancements aim to improve environmental sustainability and address the challenges posed by water pollution caused by organic dyes such as MB [ 4 , 5 ]. Researchers have explored various advanced oxidation processes (AOPs) [ 6 ], including photocatalytic degradation [ 7 ], ozonation [ 8 ], and UV/H 2 O 2 oxidation [ 9 ], to remove MB and other textile dyes from wastewater. Several researchers have modified nonwoven fabric membranes for photocatalytic degradation of MB [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%